KEDROSTIS MEDIK. (CUCURBITACEAE) IN ASIA - W.J.J.O. De Wilde; Brigitta E; E. Duyfjes (BRIN Publishing (Penerbit BRIN), 2004)
DE WILDE, W.J.J.O. & DUYFJES, BRIGITTA E.E. 2004. Kedrostis Medik. in Asia. Reinwardtia 12(2):129 – 133. — Kedrostis (Cucurbitaceae) occurs in Africa and Madagascar and comprises 4 (5) species in Asia. Of these 2 species are found in India and Sri Lanka and 2 (3) species in western Malesia. One Malesian species is for the first time included in Kedrostis here, Kedrostis bennettii (Miq.) W.J. de Wilde & Duyfjes, and one species is described as new here, Kedrostis hirta W.J. de Wilde & Duyfjes.One more Malesian species is insufficiently known to be formally described.